The Effect of CEO on Bank Efficiency: Evidence From Private Commercial Banks - Khan, Israr; Mansi, Wang; Lin, Kuen-Lin; Liu, Chi-Fang; Suanpong, Kwanrat; Ruangkanjanases, Athapol (Frontiers in Psychology, 2021)
The main purpose of this study was to analyze the effects of Chief Executive Officer (CEO) Key attributes on the financial performance of banks. Current literature gives little attention to the important characteristics of CEOs, therefore, this paper investigates the effects of characteristics of CEOs, such as education, experience, nationality, military background (MTB), and political connectedness (PC), on the financial (return on assets) performance of listed private commercial banks in Pakistan. This research sample included 20 private commercial banks of Pakistan and used Secondary data that was derived from 2011 to 2020, which contained 200 sample observations. This paper used the Fixed effect model, Normality test, Breush–Pagan, white test, multi-collinearity, and Augmented Dickey–Fuller test to investigate the study hypotheses. The main results revealed that CEO MTB and PC significantly and positively affected the financial performance of the bank. It is also found that the CEO's education and Experience have a significant and positive relationships with bank profitability. In contrast, the nationality of the CEO has no significant relationship with the financial performance of the bank.